CARA MENGUASAI ENGLISH CONVERSTION DENGAN CEPAT PADA ATLET KARATE BATAM: CARA MENGUASAI ENGLISH CONVERSTION DENGAN CEPAT PADA ATLET KARATE BATAM - Mhd. Johan; Winda Evyanto; Gaguk Rudianto (ASOSIASI IDEBAHASA KEPRI, 2021)
English is one of the world's official languages. All information is published in English and all progress and events can be known through English. Therefore, it is only natural that the sports world is also obliged to know English. Athletes will find it difficult to adapt if they don't master English. An athlete who is able to speak English so the development of his knowledge will progress more quickly. In Batam, there are a lot of kohai-kohai who don't speak English, so we tried to share a little of our knowledges to invite them how they can master English better and easily. To master English, an athlete needs language proficiency. Therefore we emphasized on our kohai-kohai so that they get used to using English in their daily life. Here we also emphasized on my kohai-kohai that they must be able to distinguish words, because in English words can affect meaning. Besides that, we also emphasized on the kohai-kohai how to pronounce the words, this is very important in mastering English. After that, how to apply those words in a sentence. The procedure for making sentences is no less important than the above. Sentences can also determine the meaning or topic to be conveyed to the interlocutors.